Comparison of Glass Carbomer, Giomer, Glass Ionomer and Resin Fissure Sealants on Permanent Molar Teeth - Bekmezoğlu, Zeliha Ercan; Güngör, Özge Erken; Karayilmaz, Hüseyin (UI Scholars Hub, 2019)
Objectives: To compare the success of the newly developed glass carbomer-based fissure sealant to resin, glass ionomer, and giomer-based fissure sealants in permanent molar teeth according to the modified United States Public Health Service criteria. Methods: Glass carbomer-based fissure sealant GCP Glass Carbomer, glass ionomer-based fissure sealant Fuji Triage, giomer-based fissure sealant Beauti Sealant, and resin-based fissure sealant prevent seal were applied using invasive/non-invasive methods to extracted human molars. Specimens were randomly assigned into three groups based on the simulated aging procedure time. Results: According to the retention score results of Group 1, the invasive giomer material yielded the highest score in the Group. The retention score results of Group 2 showed that the invasive resin subgroup had the highest alpha-score. Furthermore, we found that the invasive GIS, non-invasive giomer, and invasive giomer subgroups had similar alpha-scores within Group 2. The glass carbomer and glass ionomer cement subgroups were unsuccessful in maintaining their edge integrity, edge coloring, surface roughness, and surface coloring. Conclusion: Thus, glass ionomer cements (GIC) and glass carbomer-based materials can be useful alternatives to residual monomers contained in resin-based fissure sealants. For patients who can be controlled regularly, glass carbomer fissure sealant can be applied using invasive methods.